Investigation into overall heat transfer coefficient in indirectly heated rotary torrefier. (November 2016) - Nhuchhen, Daya Ram; Basu, Prabir; Acharya, Bishnu
Highlights: Heat transfer coefficients in rotary torrefier are investigated. Modified model for the wall to solid heat transfer coefficient has a better predictive power. Overall heat transfer coefficient model (OHTC) is verified experimentally. The OHTC values were found in a range of 13.2–20.9 W/m 2  K. Effects of angular speed, inclination, and reactor diameter are also examined. Abstract: This paper investigates into the heat transfer from the wall to solids moving inside an indirectly heated rotary reactor with flights. The cluster renewal mechanistic model was used to develop a model for estimating the effective heat transfer coefficient (EHTC) from wall to solids. The overall heat transfer coefficient (OHTC) considered the heat transfer from the reactor wall to solids, and that from the wall to gases in the reactor whose wall temperature is maintained at constant temperature. Predictions from the OHTC model showed a good agreement with values measured in the reactor fed with brass particles. The model for estimating the EHTC was compared with the published experimental values of Herz et al. (2012), and showed a better agreement than the existing models. The developed model could therefore be applied for designing rotary torrefier or used for overall performance model of rotary torrefier.